PENGARUH PENDIDIKAN POLITIK DAN PENDIDIKAN PEMILIH TERHADAP KOMPETENSI DEMOKRATIS PEMILIH PADA PEMILIHAN UMUM 2024 DI KABUPATEN MAGELANG - Satria Fawaz Miqdad; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
This study aims to analyze the influence of political education and voter education on voters' democratic competence in the 2024 General Election in Magelang Regency. The study is motivated by the high level of electoral participation at 83 percent, which has yet to be accompanied by adequate quality of voter decision-making — as evidenced by the persistence of vote-buying practices and low political literacy. The study employs an explanatory quantitative method, collecting data through questionnaires distributed to 91 respondents across 21 sub-districts using proportionate stratified random sampling. Data analysis was conducted using multiple linear regression. The results show that: (1) political education has a positive and significant effect on voters' democratic competence (B=0.489; t=6.639; sig.=0.000); (2) voter education has a positive and significant effect (B=0.488; t=4.055; sig.=0.000); and (3) both variables simultaneously have a significant effect (F=68.613; Adjusted R²=0.600), indicating that 60 percent of the variation in democratic competence is explained by both variables. A One-Way ANOVA comparative analysis based on territorial characteristics found no significant difference in democratic competence between urban, semi-urban, and rural areas (p>0.05), indicating that democratic Halaman 1 competence is geographically distributed. These findings affirm that political education and voter education are strategic instruments for promoting more substantive democracy.